Achieving accurate interpretation results from full-waveform streamed data AEM surveys. Issue 1 (1st December 2016) - Combrinck, Magdel; Wright, Richard
Abstract : Successful interpretation of airborne electromagnetic (AEM) data depends strongly, but not exclusively, on the quality of data. The ability to accurately describe the system, knowledge of the data processing procedures as well as an understanding of the geological targets all contribute to derive accurate models. Xcite ™ is a recently developed helicopter time domain electromagnetic system featuring an inflatable frame and full-waveform recording of streamed data. Working with the streamed data allows for restructuring of traditional data processing routines to customize data sets for specific applications. It also allows for a better understanding of the corrections that are required to isolate the secondary field response from measurements acquired on a helicopter platform. An accurate system description as well as transparency in the data processing phase allows interpreters to get the most value from airborne electromagnetic data.